2005
DOI: 10.1038/ng1622
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of polarized extension and planar cell polarity in the cochlea by the vertebrate PCP pathway

Abstract: The mammalian auditory sensory organ, the organ of Corti, consists of sensory hair cells with uniformly oriented stereocilia on the apical surfaces, displaying a distinct planar cell polarity (PCP) parallel to the sensory epithelium 1-3 . It is not clear how this polarity is achieved during differentiation 4-5 . Here we show that the organ of Corti is formed from a thicker and shorter postmitotic primordium through unidirectional extension, characteristic of cellular intercalation known as convergent extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
315
3
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 289 publications
(336 citation statements)
references
References 30 publications
(3 reference statements)
15
315
3
1
Order By: Relevance
“…We and others have observed the onset of Math1 in columns of cells spanning the depth of the cochlear epithelium within the primordial organ of Corti (Chen et al, 2002;Kiernan et al, 2005a;Wang et al, 2005;Fig. 2B,C), and we have hypothesized that these columns of cells are the early hair cell precursors in a multi-cell layered primordial organ of Corti at E14.5. Subsequently, cellular intercalation movements, characteristic of convergent extension (Keller, 2002), lead to the extension of the organ of Corti and the formation of a single hair cell layer during terminal differentiation (Chen et al, 2002;Montcouquiol et al, 2003;McKenzie et al, 2004;Wang et al, 2005). At the basal region of the cochlea, the presumptive hair cell precursors marked by the expression of Math1 were seen as two columns of cells, presumably at the inner hair cell and the first row of outer hair cell locations (Fig.…”
Section: Hes6 Expression Delineates the Morphogenesis Of The Hair Celmentioning
confidence: 63%
See 1 more Smart Citation
“…We and others have observed the onset of Math1 in columns of cells spanning the depth of the cochlear epithelium within the primordial organ of Corti (Chen et al, 2002;Kiernan et al, 2005a;Wang et al, 2005;Fig. 2B,C), and we have hypothesized that these columns of cells are the early hair cell precursors in a multi-cell layered primordial organ of Corti at E14.5. Subsequently, cellular intercalation movements, characteristic of convergent extension (Keller, 2002), lead to the extension of the organ of Corti and the formation of a single hair cell layer during terminal differentiation (Chen et al, 2002;Montcouquiol et al, 2003;McKenzie et al, 2004;Wang et al, 2005). At the basal region of the cochlea, the presumptive hair cell precursors marked by the expression of Math1 were seen as two columns of cells, presumably at the inner hair cell and the first row of outer hair cell locations (Fig.…”
Section: Hes6 Expression Delineates the Morphogenesis Of The Hair Celmentioning
confidence: 63%
“…Intriguingly, Math1 is expressed in a subpopulation of cells within the primordial organ of Corti as columns of cells spanning the depth of the cochlear epithelium at this stage ( Fig. 2; Chen et al, 2002;Kiernan et al, 2005a;Wang et al, 2005). We and others previously have shown that the longer and thinner mature organ of Corti is derived from a shorter and thicker postmitotic precursor domain (Ruben, 1967;Chen and Segil, 1999;Lowenheim et al, 1999), likely through cellular intercalation movements characteristic of convergent extension (Chen et al, 2002;McKenzie et al, 2004;Wang et al, 2005).…”
Section: Morphogenesis Of the Inner Ear Sensory Lineage Marked By Thementioning
confidence: 99%
“…Vangl2 mRNA shows similar expression in both locations at 14.5 dpc and 16.5 dpc (Montcouquiol et al, 2003). Celsr1, Dvl1, and Dvl2 are found in the statoacoustic ganglion (Wang et al, 2005). Unlike Cecr2, all the core PCP genes tested have also been found expressed in the sensory hair cells themselves (Wang et al, 2005;Jones and Chen, 2007;Seifert and Mlodzik, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Celsr1, Dvl1, and Dvl2 are found in the statoacoustic ganglion (Wang et al, 2005). Unlike Cecr2, all the core PCP genes tested have also been found expressed in the sensory hair cells themselves (Wang et al, 2005;Jones and Chen, 2007;Seifert and Mlodzik, 2007). However, Wnt5a expression also appears in the cochlear floor and not the hair cells (Qian et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation